Productivity of maize hybrids of different maturity under conditions of the northern Steppe of Ukraine - Котченко, М. В.; Кирсанова, Г. В.; Пугач, А. М.; Пугач, А. В. (Scientific Progress & Innovations, 2016)
We established that the highest productivity indexes (the leaf area, number of cobs per 100 plants, grain weight of one cob, weight of 1000 grains) form hybrid crops NC Lemoro. Agroclimatic potential of Steppe zone of Ukraine is in the best biological characteristics of this group of hybrids ripeness, ensuring the formation of grain yield at 8,67 tones/ha.